Remarks by World Bank Group President David Malpass at the Seventh Ministerial Meeting of the Coalition of Finance Ministers for Climate Action - Malpass, David (World Bank, Washington, DC, 2022)
This report discusses the remarks delivered by World Bank Group President David Malpass at the seventh ministerial meeting of the coalition of finance ministers for climate action. He discusses: many climate interventions and projects offer large global public good benefits but require substantial resources and compensations and may offer no financial returns. The challenge is how to incentivize these activities. As carbon markets scale, they may provide part of the flow of financial benefit to support projects that reduce carbon emissions. To address this part of the challenge, the Bank have prepared a concept note that presents pooling private sector contributions in support of greenhouse gas (GHG) emission reduction projects into a financing platform in exchange for verified carbon credits. Globally, Finance Ministries also need to catalyze the private sector to help close the financing gap for investments in mitigation and adaptation.